Timing attack analysis on AAβ cryptosystem - Abd Ghafar, Amir Hamzah; Kamel Ariffin, Muhammad Rezal (Scientific Research Publishing, 2014)
Timing attack is an attack on the implementation of a cryptographic primitive. The attack collects leaked secret data via certain implementation techniques either on software or hardware. This paper provides an analysis of a theoretical timing attack on the AAβ algorithm. The attack dis- cussed in this paper gives avenues for secure implementation of AAβ against timing attacks. The simulation of the attack is important to provide invulnerability features for the algorithm in order to be implemented and embedded on applications. At the end of the attack, a method to overcome it will be introduced and it is called AAβ blinding.